Programa residência pedagógica: relato de experiência de um residente numa escola estadual de Itacoatiara - AM - Fonseca, Mariano Marques (Brasil, 2023)
This work deals with a reflection on the activities that were developed during the Institutional Pedagogical Residency Program of the Degree in Sciences: Mathematics and Physics at the Federal University of Amazonas, Campus Itacoatiara. The purpose of the Program is to contribute to the training of students, giving them greater contact with the area of expertise, helping high school teachers and students to fill in gaps that arise during the teaching-learning process. learning. Being the first time of the Residency at the Institute of Exact Sciences and Technology (ICET), which began at the end of 2020, the choice of the experience report is justified by allowing the student, through greater contact with school routine, describing the most relevant experiences for their education, exposing their difficulties and maturing of ideas and thoughts throughout the activities developed, aiming to contribute both to future studies related to research and to the practice of future residents. Based on this, we sought, through this work, to reflect on the activities that were developed in a state school in the municipality of Itacoatiara - AM, presenting the contributions that the Pedagogical Residency Program (PRP) brings to the initial training of teachers( as), as well as demonstrating the ways in which these activities are carried out. For this, in the methodological aspect of this personal report, we used a qualitative approach supported by a literature review, among which are cited: Ausubel (1980); Carvalho (2018); D'Ambrosio (1988); Libâneo (1999) and Pimenta (2006). In this way, the elaborations of the experience reports that preceded this Course Completion Work, allowed to describe the educational reality of the participating school, mainly through the work carried out in the context of the epidemiological problem (Covid-19) faced in the period of the Residency. The activities covered Emergency Remote Teaching (ERE), hybrid teaching and face-to-face teaching. In this way, we believe to strengthen the debate regarding the importance of the free public School-University relationship, and the guarantee of the right to quality education, in addition to allowing the search for new knowledge and methods that contribute to the teaching-learning process, improving the praxis of teachers in training, regarding the teaching of Mathematics and Physics.